Conversion of Sewage Sludge into Biofuels via Different Pathways and Their Use in Agriculture: A Comprehensive Review - Zygmunt Kowalski; Agnieszka Makara; Joanna Kulczycka; Agnieszka Generowicz; Paweł Kwaśnicki; Józef Ciuła; Anna Gronba-Chyła (Energies, 2024)
The valorisation of sewage sludge for sustainable agricultural use and biofuel production proposes an effective and beneficial management of sewage sludge in a closed-loop cycle. The management of sewage sludge biowaste is a rising problem due to increasing waste storage expenses. In this sense, the use of circular economy principles in sewage sludge management creates opportunities to develop new technologies for processing. The biorefinery model allows the application of wasteless technologies via sewage sludge valorisation in terms of agricultural use and biofuel production, especially with the hydrothermal carbonisation method. Applying hydrothermal carbonisation in the treatment of biosolid sewage sludge has numerous benefits due to processing highly hydrated organic waste into carbon hydro char, a high-quality solid biofuel. The direct use of sewage sludge in the soil does not allow for full use of its functional properties. However, the hydrothermal carbonisation of sewage sludge results in biocarbon pellets, making it a viable approach. This work also discusses the barriers (legal, chemical, biological, and technical) and possibilities related to sewage sludge biorefining processes.